THE INTERPRETER-TRANSLATOR IN FRENCH COURTS: LITERAL TRANSLATION OR COMPARATIVE LAW? - Tulekian, Isabelle (2014)
This paper is about the role of the interpreter-translator at court in France and the relevance of the judge regarding the relation between language and law, at a time when forensic linguistic turns more and more obvious the frequent and difficult relations between legal translation and comparative law.